The Revitalization of Tugu Silalahi Batak Toba Folklore into Teaching Materials in English Subject for Junior High School - Rosalia Indah Ginting; Bambang Nur Alamsyah Lubis; Dayfirna Angelia Sinaga (Linguistic, English Education and Art (LEEA) Journal, 2021)
The objective of this research is to revitalize the Batak Toba folklore Tugu Silalahi as learning material in junior high school. The aims to find out the original story of batak toba folklore “Tugu Silalahi”. This research used descriptive qualitative. The researchers conducting interviews with the community in Silalahi village as an instrument for collecting data from interviews obtained by the researcher. The result showed that the silalahi story was true, indicated by existance of a monument as a form of respect for Raja Silalahi. And then researcher making a story script which is used as material. Keywords: Folklore, Revitalization, Teaching Material.